Pragmatic Analysis of Expressive Speech Acts in Tweets by Arab Figures on Twitter: Strategic Management Insights - Fathoni, Ahmad; Halifa, Nur; Maksum, M. Syukron; Aminudin (Journal of Educational Management Research, 2025)
This study examines expressive speech acts in the tweets of Arab figures on Twitter throughout 2022, focusing on categories such as gratitude, congratulations, condolences, happiness, and pride. Expressive speech acts play a crucial role in reflecting the psychological states of speakers and highlighting cultural values, religiosity, and social ethics inherent in Arab society. The research uses a qualitative descriptive method, analyzing tweets from prominent figures like King Salman and the Minister of Defense, among others. Data was collected through observation of Arabic-language tweets, identifying and classifying expressive speech acts. The findings show that these speech acts are not only used for personal expression but also strategically to reinforce national identity and public image. They serve as tools for managing public relations, fostering social cohesion, and maintaining trust between leaders and the public. While the study offers valuable insights into Arabic-language social media, its scope is limited to tweets in 2022. Future research could expand the analysis to other platforms and explore the influence of political and social contexts. This research contributes to the field of pragmatics and digital communication studies.